Improving Accounting Literacy Through Practice-Based Training in Accounting Vocational Education - Eka Siskawati; Novrina Chandra; Firman Surya; Fitra Oliyan; Rini Frima; Welsi Haslina (Carmin: Journal of Community Service, 2026)
This study aims to enhance the basic accounting literacy of tenth-grade students at SMKN 3 Padang. The Practice-Based Training (PBT) method, a pedagogical approach that emphasises experiential and iterative learning, was used to achieve objectives of the study. Conducted over two structured sessions, the training integrated concept briefing, guided practice, independent exercises, and performance review of simple transaction recording. Quantitative results from pre- and post-tests involving 35 students revealed substantial improvements across all measured dimensions. Qualitative observations further indicated increased student engagement, improved communication with facilitators, and greater persistence during practice tasks. These findings demonstrate that PBT effectively bridges the gap between theoretical instruction and practical application in vocational accounting education. While the study was limited by its short intervention period and single-site implementation, it provides meaningful contributions to the development of practice-centered instructional models that support workforce readiness.